The Workforce Development Through Increased Work Productivity - Sunkad, Gayatri (Riviera Publishing, 2022)
Introduction: Production is a significant concept in the modern era. It can be classified as economic Production, Production in food grains and Production is also related to labor, labor organizational raw materials; Production in the economic sector signifies the country's wealth. Production mainly depends on the organization of labor as well. If the organization can influence the workforce, it will also positively affect the work culture. The production also depends on labor because they are two sides of the same coin. Without labor, there is no production appraisal either. Methods: This study uses a literature review research design. Search articles discussed in the study using several databases. Result: Without labor, there can be no production, and the two are interrelated. Production is like the oxygen of a nation's economic system and is the basis of an organized society. For qualitative Production, a well-equipped workforce is needed to increase production growth. Conclusion: Productivity and labor are fundamentally influential parts of economic development.